Simulation of Topography Effects on Rockfall‐Generated Seismic Signals: Application to Piton de la Fournaise Volcano. Issue 10 (10th October 2020) - Kuehnert, J.; Mangeney, A.; Capdeville, Y.; Métaxian, J. P.; Bonilla, L. F.; Stutzmann, E.; Chaljub, E.; Boissier, P.; Brunet, C.; Kowalski, P.; Lauret, F.; Hibert, C.
Abstract: Seismic waves generated by rockfalls contain valuable information on the properties of these events. However, as rockfalls mainly occur in mountainous regions, the generated seismic waves can be affected by strong surface topography variations. We present a methodology for investigating the influence of topography using a Spectral‐Element‐based simulation of 3‐D wave propagation in various geological media. This methodology is applied here to Dolomieu crater on the Piton de la Fournaise volcano, Reunion Island, but it can be used for other sites, taking into account local topography and medium properties. The complexity of wave fields generated by single‐point forces is analyzed for different velocity models and topographies. Ground‐motion amplification is studied relative to flat reference models, showing that Peak Ground Velocity (PGV) and total kinetic energy can be amplified by factors of up to 10 and 20, respectively. Simulations with Dolomieu‐like crater shapes suggest that curvature variations are more influential than depth variations. Topographic effects on seismic signals from rockfalls at Dolomieu crater are revealed by interstation spectral ratios. Results suggest that propagation along the topography rather than source direction dominates the spectral ratios and that resulting radiation patterns can be neglected. The seismic signature of single rockfall impacts is studied. Using Hertz contact theory, impact force and duration are estimated and then used to scale simulations, achieving order‐of‐magnitude agreement with observed signal amplitudes and frequency thresholds. Our study shows that combining Hertz theory with high‐frequency seismic wave simulations on real topography improves the quantitative analysis of rockfall seismic signals. Key Points: First‐ever simulation of high‐frequency rockfall seismic waves using the 3D Spectral Element Method Ground‐motion amplification induced by volcano topography found to be dependent on soil properties and rockfall position Simulations and observations successfully compared by means of inter‐station spectral ratios and Hertz theory